Differential Expression of Matrix Metalloproteases in Human Fibroblasts with Different Origins - Diana Lindner; Christin Zietsch; P. Moritz Becher; Karsten Schulze; Heinz-Peter Schultheiss; Carsten Tschöpe; Dirk Westermann (Biochemistry Research International)
Fibroblasts are widely distributed cells and are responsible for the deposition of extracellular matrix (ECM) components but also secrete ECM-degrading matrix metalloproteases. A finely balanced equilibrium between deposition and degradation of ECM is essential for structural integrity of tissues. In the past, fibroblasts have typically been understood as a uniform cell population with comparable functions regardless of their origin. Here, we determined growth curves of fibroblasts derived from heart, skin, and lung and clearly show the lowest proliferation rate for cardiac fibroblasts. Furthermore, we examined basal expression levels of collagen and different MMPs in these three types of fibroblasts and compared these concerning their site of origin. Interestingly, we found major differences in basal mRNA expression especially for MMP1 and MMP3. Moreover, we treated fibroblasts with TNF-α and observed different alterations under these proinflammatory conditions. In conclusion, fibroblasts show different properties in proliferation and MMP expression regarding their originated tissue.